2012
DOI: 10.1097/brs.0b013e318227dd0c
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Leptin Bioavailability in Adolescent Idiopathic Scoliosis

Abstract: This is the first study demonstrating the presence of abnormal leptin bioavailability in AIS girls that might play an important role in the etiopathogenesis of AIS. Further investigation is required to provide a better understanding of the underlying mechanisms, with the aim to explore the potential clinical application as a biomarker for predicting curve initiation or progression in AIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
51
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 44 publications
4
51
0
6
Order By: Relevance
“…4,26 AIS girls recruited in this study showed altered free leptin bioavailability with higher sOB-R levels, and lower FLI ( Table 2); the results are consistent with our previous studies that included different and smaller cohorts. 8,9 In addition to deranged bone quality, lower body weight, and lower BMI, 8,9 this study indicated that the altered free leptin bioavailability in AIS girls is also associated with lower body fat and lower skeletal muscle mass, which provided additional evidence that the functions of leptin could be affected under the pathological conditions of AIS. Leptin is mainly produced by adipose tissues and was shown to strongly and positively correlate with BFM and %BF in the healthy population.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…4,26 AIS girls recruited in this study showed altered free leptin bioavailability with higher sOB-R levels, and lower FLI ( Table 2); the results are consistent with our previous studies that included different and smaller cohorts. 8,9 In addition to deranged bone quality, lower body weight, and lower BMI, 8,9 this study indicated that the altered free leptin bioavailability in AIS girls is also associated with lower body fat and lower skeletal muscle mass, which provided additional evidence that the functions of leptin could be affected under the pathological conditions of AIS. Leptin is mainly produced by adipose tissues and was shown to strongly and positively correlate with BFM and %BF in the healthy population.…”
Section: Discussionmentioning
confidence: 90%
“…6 It is thus logical to investigate into the possible role of leptin in the etiopathogenesis of AIS. In previous studies, abnormal leptin bioavailability with increased levels of soluble leptin receptor (sOB-R) was found in AIS girls, 8 which was found to be associated with deranged bone quality. 9 A recent animal study has reported that high central leptin activity could increase the risk of developing scoliosis.…”
mentioning
confidence: 97%
“…(38,39) One study found low leptin levels in those with scoliosis even after adjusting for body weight, but they were unable to adjust for fat mass specifically. (38) This is important because leptin is secreted from fat mass. The other study found that the low leptin identified in girls with scoliosis was not independent of body weight or BMI.…”
Section: Discussionmentioning
confidence: 99%
“…13 In current study, we observed that AIS patients had significantly higher frequency of both TT genotype and T allele of rs2767485 polymorphism in LEPR gene than normal controls, which supported our prior fi nding that patients with AIS have signifi cantly higher sOB-R level than normal healthy girls. 7 As the main binding protein for leptin in the circulation, sOB-R might affect the leptin bioavailability to the cells by competing with membrane-anchored LEPR and inhibiting the transport of free leptin into cells and across the blood-brain barrier. 12 , 20 , 21 Hence, we can infer that dysfunction of LEPR gene may induce abnormal leptin bioavailability by affecting the expressing level of sOB-R.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, girls with AIS were found to have higher soluble leptin receptor (sOB-R) levels and lower free leptin index in peripheral blood, which prompted the abnormal leptin bioavailability in these patients. 7 In another recent cytological study, Liang et al 8 emphasized the potential role of leptin signaling in the etiopathogenesis of AIS.…”
mentioning
confidence: 98%